2007
DOI: 10.1017/s0022112007006842
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation analysis of mechanisms for viscous losses in a turbomachinery tip-clearance flow

Abstract: The tip-leakage flow in a turbomachinery cascade is studied using large-eddy simulation with particular emphasis on understanding the underlying mechanisms for viscous losses in the vicinity of the tip gap. Systematic and detailed analysis of the mean flow field and turbulence statistics has been made in a linear cascade with a moving endwall. Gross features of the tip-leakage vortex, tip-separation vortices, and blade wake have been revealed by investigating their revolutionary trajectories and mean velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(81 citation statements)
references
References 43 publications
2
78
1
Order By: Relevance
“…You et al (2006) investigated the effect of tip-gap size on the tip-leakage vortical structures and velocity and pressure fields using LES computation. Simultaneously, the mechanisms for viscous losses in a turbomachinery tip-leakage flow was revealed by You et al (2007). He concludes that the velocity gradients are the major source for viscous losses in the cascade endwall region, and an approach which can alleviate the viscous losses through changing the direction of the tip-leakage flow was proposed.…”
mentioning
confidence: 99%
“…You et al (2006) investigated the effect of tip-gap size on the tip-leakage vortical structures and velocity and pressure fields using LES computation. Simultaneously, the mechanisms for viscous losses in a turbomachinery tip-leakage flow was revealed by You et al (2007). He concludes that the velocity gradients are the major source for viscous losses in the cascade endwall region, and an approach which can alleviate the viscous losses through changing the direction of the tip-leakage flow was proposed.…”
mentioning
confidence: 99%
“…At the same region, the most intensive pressure fluctuations These complicated vortexes have a remarkable influence on the flow pattern. Studies on the mechanisms of viscous losses [39][40][41] show that the TLV and leakage flow can lead to violent turbulence intensity, which increases the viscous losses near the tip clearance. Using the results from numerical simulation, You et al proposed strategies to improve the engineering design, such as optimizing the direction of leakage flow by changing the tip shape.…”
Section: Vortex Types and Corresponding Characteristicsmentioning
confidence: 99%
“…Therefore, the flow field near the rotor blade is emphatically analyzed as follows. You et al [2007] found that the tip vortex structure of ducted propeller is formed by three parts: the tip-separation vortex, the tip-leakage vortex and the induced vortex. The tip-leakage vortex is caused by the pressure difference between the pressure and the suction side.…”
Section: Effects Of Different Tip Clearances On the Open Water Performentioning
confidence: 99%